Neural Representation. A Survey-Based Analysis of the Notion - Vilarroya, Oscar (Frontiers in Psychology, 2017)
The word representation (as in "neural representation"), and many of its related terms, such as to represent, representational and the like, play a central explanatory role in neuroscience literature. For instance, in "place cell" literature, place cells are extensively associated with their role in "the representation of space." In spite of its extended use, we still lack a clear, universal and widely accepted view on what it means for a nervous system to represent something, on what makes a neural activity a representation, and on what is re-presented. The lack of a theoretical foundation and definition of the notion has not hindered actual research. My aim here is to identify how active scientists use the notion of neural representation, and eventually to list a set of criteria, based on actual use, that can help in distinguishing between genuine or non-genuine neural-representation candidates. In order to attain this objective, I present first the results of a survey of authors within two domains, place-cell and MVPA research. Based on the authors' replies, and on a review of neuroscientific research, I outline a set of common properties that an account of neural representation seems to require. I then apply these properties to assess the use of the notion in two domains of the survey, place-cell and MVPA studies. I conclude by exploring a shift in the notion of representation suggested by recent literature.